Internet Sehat dan Aman di Era Pandemik Bagi Masyarakat - Herman Saputra; Nofriadi Nofriadi; Adi Prijuna; Bachtiar Efendi (Smart Education, 2021)
Abstract:The development of the internet that is getting faster makes it easier for humans to disseminate and receive/search for information without being bound by national borders in the international scope. Now humans have lived in practicality considering that increasingly modern means of communication to support all activities are available, even the presence of the internet is able to provide data on various kinds of information, ranging from political, economic, social, cultural and so on, simply through search engines. search engine) then the required information will be obtained. Even through the internet, information for personal life can be obtained such as health, recreation, hobbies, personal development, spiritual and others. But there is another part that needs to be understood that the presence of internet media with the offer or choice of various sites with the freedom of access is like a double-edged sword, on the one hand can have a positive impact and on the other hand a negative impact. One of them that is currently rife is hoaxes, cyberbullying and even cybercrime. Keywords: Healthy Internet; cyberbullying; cybercrime Abstrak:Perkembangan internet yang semakin cepat mempermudah manusia untuk menyeba-rluaskan dan menerima/mencari informasi tanpa terikat batas negara dalam lingkup internasional. Kini manusia sudah hidup dalam kepraktisan mengingat sarana komunikasi semakin modern sebagai penunjang segala kegiatan telah tersedia, bahka kehadiran internet mampu menyediakan data berbagai ragam informasi, mulai dari politik, ekonomi, sosial, budaya dan sebagainya cukup melalui search engine (mesin pencari) maka informasi yang dibutuhkan akan didapatkan. Bahkan melalui internet, informasi untuk kehidupan pribadi bisa diperoleh seperti kesehatan, rekreasi, hobi, pengembangan pribadi, rohani dan lainnya. Tetapi ada bagian lain yang perlu dipahami bahwa kehadiran media internet dengan tawaran atau pilihan beragam situs dengan keleluasaan akses seperti pedang bermata dua, di satu sisi bisa membawa dampak positif dan di sisi lain berdampak negatif. Sala satunya yang marak saat ini adalah hoax, cyberbullying dan bahkan cybercrime. Kata kunci: Internet Sehat; cyberbullying; cybercrime